MAKNA SIMBOLIK GAPURA PERB ATASAN GOWA MAKASSAR DI HERTASNING BARU - Fatahuddin; Tangsi; Muhammad faisal (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2024)
The purpose of this study is to determine the symbolic meaning of the Gowa–Makassar border gate located on Hertasning Baru Street. The data collection techniques used were observation, interviews, and documentation. This research aims to provide a clear, accurate, and comprehensive description of the “Symbolic Meaning of the Gowa–Makassar Border Gate at Hertasning Baru.” The method employed in this study was a survey method conducted through direct observation. Data analysis was carried out by collecting the results of observations, interviews, and documentation (photographs), followed by data categorization and interpretation. Important data were summarized, organized into sections, verified for accuracy, and then interpreted. The samples in this study consisted of several photographs of the Gowa–Makassar border gate at Hertasning Baru. Based on the research findings, it can be concluded that the visual form of the Gowa–Makassar border gate emphasizes the shape of the badik, which is a traditional weapon characteristic of the Gowa community.